2021
DOI: 10.1101/2021.02.01.20232785
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased circulating levels of angiotensin-(1-7) in severely ill COVID-19 patients

Abstract: The mono-carboxypeptidase Angiotensin-Converting Enzyme 2 (ACE2) is an important player of the renin-angiotensin system (RAS). ACE2 is also the receptor for SARS-CoV-2, the new coronavirus that causes COVID-19. It has been hypothesized that following SARS-CoV-2/ACE2 internalization Ang II level would increase in parallel to a decrease of Ang-(1-7) in COVID-19 patients. In this preliminary report, we analyzed the plasma levels of angiotensin peptides in 19 severe COVID-19 patients and 19 non-COVID-19 volunteers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 11 publications
0
31
1
Order By: Relevance
“…Patients with severe COVID-19 illness had significantly increased circulating levels of angiotensin 1-7 and decreased angiotensin II [82,83]. The angiotensin 1-7/angiotensin II ratio was 3-fold higher in COVID-19 patients as compared to that in healthy controls, thus suggesting an increased activity of ACE2 or other angiotensin 1-7 forming activity after COVID-19 infection [82]. Although TOP is an important angiotensin 1-7 forming factor, expression or activity of TOP in COVID-19 patients have not been analyzed.…”
Section: Effects Of Top In Intracellular Processing Of Angiotensin 1-7 and Its Potential Involvement In Covid-19 Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with severe COVID-19 illness had significantly increased circulating levels of angiotensin 1-7 and decreased angiotensin II [82,83]. The angiotensin 1-7/angiotensin II ratio was 3-fold higher in COVID-19 patients as compared to that in healthy controls, thus suggesting an increased activity of ACE2 or other angiotensin 1-7 forming activity after COVID-19 infection [82]. Although TOP is an important angiotensin 1-7 forming factor, expression or activity of TOP in COVID-19 patients have not been analyzed.…”
Section: Effects Of Top In Intracellular Processing Of Angiotensin 1-7 and Its Potential Involvement In Covid-19 Pathogenesismentioning
confidence: 99%
“…Recent studies have found a potential link between angiotensin 1-7 and COVID-19 pathophysiology [82,83]. Patients with severe COVID-19 illness had significantly increased circulating levels of angiotensin 1-7 and decreased angiotensin II [82,83].…”
Section: Effects Of Top In Intracellular Processing Of Angiotensin 1-7 and Its Potential Involvement In Covid-19 Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…The observed overactivation of the non-classical RAS axis is expected to yield an increase of circulating Ang-(1-5), obtained by cleavage of Ang-(1-7) by ACE (Figure 1). Yet opposite trends are found for the levels of circulating Ang-(1-5) measured in two studies: a reduction of about 80% in the COVID-19 class with respect to controls [84], or a 100% increase [80] (see Supplementary Table S1).…”
Section: Meta-analysis On Ras Components In Covid-19mentioning
confidence: 76%